Specific Performance of Unfulfillable Plea Bargains - Gasner, Stuart L. (1980)
This article discusses how courts have handled the remedy dilemma presented by unfulfillable plea bargains. Part I analyzes the seminal Supreme Court opinion on the broken plea bargain question, Santobello v. New York. This section concludes that choice-of-remedy is not entirely a matter of lower court discretion. Rather, Santobello delegates to lower courts the authority to develop a law of remedies which conforms to the underlying principles of that decision. Part I also focuses on what courts have done with this mandate, discussing the elements of decision courts have developed to remedy unfulfillable plea bargains. Finally, Part II suggests a model analysis, requiring a presumption of specific performance when the defendant can show detrimental reliance on the unfulfillable bargain